Psychology of Dream by Ibn Sirin’s Perspective/Psikologi Mimpi Ibnu Sirin - Jamaluddin, Muhammad (Psikoislamika: Jurnal Psikologi Islam, 2020)
Dreams are considered as an influence of physical activity and a reflection of the psychiatric symptoms experienced by individuals. Dreams can give positive and negative impact for individuals. This study aims to explain the psychology of dreams from Ibn Sirin's perspective. A qualitative method by literature study approach, specifically the dream psychology in the perspective of Ibn Sirin was employed in this study. The results showed that this dream came not only from the subconscious dimension, but also came from a further and transcendental dimension (such as dreams experienced by prophets or sholeh people by all interpretations). As stated by Ibn Sirin, dreams can serve as a means to evoke pent-up feelings that cannot be expressed in conscious time and are the symbolic representations of spiritual life derived from transcendental dimensions.Keywords: Psychology; Dreams; Ibn SirinMimpi dianggap sebagai pengaruh dari aktivitas fisik dan cerminan dari gejala kejiwaan yang dialami oleh individu. Mimpi dapat memberikan dampak yang positif maupun negatif terhadap individu. Tujuan penelitian ini yakni untuk menjelaskan psikologi mimpi dari perspektif Ibnu Sirin. Penelitian ini menggunakan kualitatif dengan pendekatan studi literatur, psikologi mimpi dalam perspektif ibnu sirin. Hasil penelitian menunjukkan jika mimpi ini tidak hanya berasal dari dimensi bawah sadar saja, namun juga bersumber dari dimensi yang lebih jauh dan bersifat transendental (seperti mimpi yang dialami oleh nabi atau orang sholeh dengan segala penafsirannya). Menurut Ibnu Sirin, mimpi dapat berfungsi sebagai sarana untuk memunculkan perasaan yang terpendam yang tidak dapat diungkapkan pada waktu sadar serta merupakan representasi simbolis dari kehidupan spiritual yang bersumber dari dimensi transendental.Kata Kunci: Psikologi; Mimpi; Ibnu SirinÂ